Analisis CSR Disclosure, Green Innovation dan Profitabilitas Terhadap Nilai Perusahaan - Estuti, Eni Puji; Putri, Handayani (STIE Semarang, 2024)
Company value (company value) is the basis for prospective investors because the company value will reflect the condition of the company. . It is important for investors to focus on company value because this is the goal of investors investing in profitable companies. The method used is a quantitative method using classical assumption tests and multiple regression tests. The results of this study indicate that the CSR Index and Green Innovation have no effect on Company Value. While Return On Assets has a positive and significant effect on Company Value in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022.